TEOLOGI PRIBUMI DI INDONESIA - Yonky Karman (Jurnal Amanat Agung, 2022)
Abstract: One of the problems with the indigenization of Christian theology in Indonesia is how to respond positively to the Indonesian context. This problem is inseparable from Indonesian theologies which in many respects depend on the final product of Western theologies, a dependence on doing theology without independence and creativity. To overcome this dependence and at the same time foster theological independence, it is first important to reposition the passive subject of doing theology into an active subject by adopting a cultural approach (constructive orientalism). Second, getting rid of the tendency to disbelieve in local elements by reviewing the "kafir" vocabulary of Indonesian Bible texts because these inaccurate  translations indirectly  reinforce  this  tendency.  Within  the context of  the  church and  society, the  path  of  indigenous theology branches off, either through biblical studies or directly through existing church theology. Keywords: indigenization, kafir, independence, Bible, theology. Abstrak: Salah satu problem pribumisasi teologi Kristen di Indonesia adalah bagaimana merespons positif konteks keindonesiaan. Problem ini tak terlepas dari teologi-teologi Indonesia yang dalam banyak hal bergantung pada produk akhir teologi-teologi Barat, suatu ketergantungan berteologi tanpa kemandirian dan  kreativitas. Untuk mengatasi  ketergantungan  ini  sekaligus  menumbuhkan  kemandirianberteologi,  pertama-tama pentinglah  reposisi subjek  pasif  berteologi menjadi subjek  aktif  dengan  mengadopsi suatu  pendekatan budaya (orientalisme konstruktif). Kedua, menyingkirkan kecenderungan mengafirkan unsur-unsur lokal dengan mengkaji kosakata “kafir” teks-teks Alkitab bahasa Indonesia karena terjemahan yang tak tepat ini secara tidak langsung memperkuat kecenderungan tersebut. Dalam bingkai konteks gereja dan masyarakat, jalan berteologi pribumi bercabang, bisa lewat studi biblika atau langsung lewat teologi gereja yang ada. Kata-kata Kunci: pribumisasi, kafir, kemandirian, Alkitab, teologi.